Analisis dokumen silibus kimia organik matrikulasi berdasarkan taksonomi bloom - Othman, Azraai; Talib, Othman; Ibrahim, Dani Asmadi (Faculty of Education, University of Malaya, 2015)
This article reports on a qualitative study based on document analysis to characterize the teaching and learning of Matriculation Organic Chemistry, Ministry of Education based on the revised Bloom’s Taxonomy. Document analysis was conducted on three elements: a description of the syllabus, questions of tutorials exercise and final examination questions. From the analysis of documents based on Bloom’s Taxonomy, it was found that the three elements are concentrated at low cognitive level. This study also identified a significant gap between the three objectives of the course: enable students to master the basic concepts of chemistry; develop science and problem-solving skills; allow students to use their knowledge and skills in new situations and daily life, with what is shown by the documents analyzed. This article also proposes an explanation that this gap is due to the traditional view of education that fails to see chemistry education as a holistic framework, and suggests steps to improve the teaching and learning of the topics studied.